Assessing How Rewards and Sanctions Shape Employee Performance at Rocky Plaza Hotel in Padang - Yandri, Melani Sefrita; Alfian, Alfian (Universitas Tanjungpura, 2024)
This study investigates the implications of reward and punishment mechanisms on employee performance, focusing on the unique context of Rocky Plaza Hotel in Padang. Drawing on insights from organizational psychology and management studies, the study explores the dynamics between reward and punishment strategies and their influence on the hotel's workforce. The research employs a quantitative approach, involving data collection from 121 hotel employees through direct communication, questionnaires, interviews, and documentation. The study establishes the significance of effective reward systems in enhancing employee motivation and job satisfaction, contributing to improved performance and productivity. Conversely, the application of sanctions or punishments is found to deter undesirable behaviors, fostering a more disciplined and efficient work environment. The hotel implements a range of reward systems, including recognition programs, performance bonuses, and promotions, along with various forms of punishments such as verbal or written warnings, salary deductions, and demotions. The study recommends fostering a supportive work environment through leadership initiatives and suggests avenues for future research to explore additional variables and alternative research methods.